Development of a Biopesticide for the Control of Schyzophyllum Commune Fr., a Pathogen of Oil Palm Seeds - Dikin, Antarjo (2007)
An effective and efficient biopesticide produced from antagonistic bacteria was developed for the control of Schizophyllum commune Fr., an important seedborne pathogen of oil palm causing brown germ and seed rot disease. Fifty two out of 265 bacterial isolates were found to inhibit the growth of S. commune in dual culture assay and 14 out of these 52 isolates produced antimicrobial substances and inhibited the growth of S. commune. Finally, 2 isolates, Burkholderia multivorans RU50 and Microbacterium testaceum RU7 were confirmed to produce a broad spectrum of antimicrobial substances in liquid media containing neopeptone plus lactose (1:1) and peptone plus maltose (1:1) respectively that were able to suppress S. commune and other species of fungi. The mixture of equal amount of supernatant containing antimicrobial substances from both bacterial species resulted in the potential biopesticide. The potential biopesticide destroyed cell organs of the fungus. It contained pyrrolnitrin, phenylpyrrol, phenazine and 5 unknown compounds. It had a minimum inhibitory concentration (MIC) value of 1:65 in the liquid form and 1:310 in freeze dried powder form. It was also resistant to heat at 60oC for 2 hours, stable under irradiation of UV light at 312 nm for 5 hours, stable in sodium chloride solution up to 10%, stable on variable of pH 4-9 and had a shelf life of up to one year at 26±2oC and 5-10oC. Application of this biopesticide with a dilution of 1:4 with distilled water, as seed treatment to oil palm seeds was effective for the control of S. commune using vacuum infiltration at 400 mm Hg Vac. for 2 minutes or seed dipping for 30 minutes for non-germinating oil palm seeds. Oil palm seeds coated with the freeze dried talcum powder inhibited the colonization of S. commune on the seeds. Oil palm seeds treated with this biopesticide increased seed germination up to 77%.